2013
DOI: 10.1080/19338244.2013.763758
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Burnout With Personality, Alexithymia, and Coping Behaviors Among Physicians in a Semiurban and Rural Area in Turkey

Abstract: This present study aimed to assess levels of burnout, to investigate the extent to which personal characteristics and coping behaviors are related to burnout, and to establish the predictors of burnout among physicians in a semiurban and rural area. A sample of 139 physicians was assessed using the Maslach Burnout Inventory, Eysenck Personality Questionnaire, Toronto Alexithymia Scale, and Ways of Coping Inventory. The level of burnout was found to be moderately higher than those reported among urban physician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 31 publications
6
23
0
4
Order By: Relevance
“…This study finding was consistent with findings of previous studies (Tominaga et al, 2014, Taycan, Taycan, & Celik, 2014 A c c e p t e d M a n u s c r i p t et al, 2008) and suggested that alexithymia during fertility treatment was associated with maladaptive coping strategies.…”
Section: Discussionsupporting
confidence: 95%
“…This study finding was consistent with findings of previous studies (Tominaga et al, 2014, Taycan, Taycan, & Celik, 2014 A c c e p t e d M a n u s c r i p t et al, 2008) and suggested that alexithymia during fertility treatment was associated with maladaptive coping strategies.…”
Section: Discussionsupporting
confidence: 95%
“…Due to the demands of medical education, including work overload, frequent examinations, and a competitive environment, medical students confront an array of intense emotions and are at high risk of developing mental disorders such as anxiety [15], depression [16], and burnout [17]. Alexithymia is a risk factor that increases vulnerability to these same disorders [1821]. Thus, the level of alexithymia among medical students is of great concern and signals the necessity for a higher level of focus on this problem.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, individual factors such as age, gender, education level, marital status, time span in the profession and seniority or psychological factors such as personality traits, and coping mechanisms have been reported as responsible factors (3,4), whereas in some others; organizational factors such as the workload, reward, control, sense of belonging and fairness are implied as responsible factors (5,6).…”
Section: Introductionmentioning
confidence: 99%